Efficient in vitro regeneration of mustard via organogenesis for genetic transformation applications - Islam, M M; Nadim, M K A; Sarkar, S; Khan, T Z; Emon, R M; Khatun, F (Bangladesh Journal of Nuclear Agriculture, 2025)
The third-most significant edible oil crop is mustard (Brassica spp.), which is a part of the genus Brassica and the family Brassicaceae (Cruciferae). Global demand for edible oil and biofuels is rising as a result of rising world population and industrialization. An efficient in vitro regeneration protocol was developed for Brassica spp. through direct and indirect organogenesis from hypocotyl, cotyledon and cotyledonary nodal segment. Murashige and Skoog medium (MS) medium with different concentrations and combinations of plant growth regulators were used for multiple shoot regeneration in three genotypes of mustard namely BARI Sarisha-14, Binasarisha-4 and Binasarisha-9. Explants were inoculated on supplemented with various concentrations and combinations of NAA, BAP, AgNO3, GA3, and IBA for callus induction, shoot initiation, shoot outgrowth, and root initiation. For In vitro regeneration, cotyledonary nodes performed the best with 100% in Binasarisha-4, 98.33% in BARI Sarisha-14 and 91.67% in Binasarisha-9. Binasarisha-4 demonstrated 76.67% callus induction, 70.83% shoot initiation, 91.82% shoot outgrowth, and 40% root initiation with hypocotyl, followed by BARI Sarisha-14 (76.67%, 58.33%, 75.00%, and 23.33%, respectively) and Binasarisha-9 (52.78%, 47.78%, 49.04%, and 11.11%). After proper hardening the in vitro regenerated plantlets were successfully transplanted into soil. Interestingly some of the in vitro regenerated shoots produced early flowers on rooting media. Bangladesh J. Nuclear Agric., 39(1): 47-59, 2025